Pengaruh Kepemimpinan Transformasional terhadap Kepercayaan kepada Pimpinan dan Performa Individu - Johan Triyadi; Ardian Adhiatma (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to provide empirical analysis regarding transformational leadership, trust in leaders and individual performance, this can be a source of reference for the development of soft skills in the leadership theme, especially restaurant managerss. The current literature is scarce on the role of leadership in enhancing leader trust and individual performance in the restaurant industry. The sample in this study was 233 crew and restaurant staff used to assess their leaders, namely restaurant managers and analyzed using SEM PLS 3. The results showed a positive and significant influence between transformational leadership and trust in leaders, and individual performance. And trust in leaders also has a positive and significant effect on individual performance. In addition, the charisma and inspirational factors of leaders contribute strongly to increasing the ability and integrity of crew and staff in influencing individual benefits and outcomes. Keywords: Transformational Leadership, Trust in Leaders, Individual Performance, Restaurant